2014
DOI: 10.1007/s13178-014-0168-3
|View full text |Cite
|
Sign up to set email alerts
|

Researching Prostitution and Sex Trafficking Comparatively

Abstract: This article examines different types of comparative research designs as applied to either prostitution or sex trafficking. I first present several comparative approaches that are found to be deeply flawed either because of the problematic assumptions of the analysts or because the data provided are insufficient to support the conclusions drawn. I then review research designs that compare two to four cases in depth and have the potential to yield stronger evidence-based findings and richer theoretical insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…6 In five polls taken between 2011 and 2013, 70% to 82% of French respondents disapproved of the idea of criminalizing clients, and a 2013 poll reported that 74% of the French public favored the “reopening of brothels” in the country (Weitzer, 2015). …”
mentioning
confidence: 99%
“…6 In five polls taken between 2011 and 2013, 70% to 82% of French respondents disapproved of the idea of criminalizing clients, and a 2013 poll reported that 74% of the French public favored the “reopening of brothels” in the country (Weitzer, 2015). …”
mentioning
confidence: 99%
“…Others theorize that criminalization can reduce prevalence, but only with certain conditions (Immordino & Russo, 2015). Comparative research tends to focus on largely negative implications of specific elements of criminalization for sex workers’ safety, outcomes or behaviors (Harcourt et al, 2010; Skilbrei & Holmstrom, 2013; Sullivan, 2010; Wagenaar, 2017; Weitzer, 2015) or the relationship between different laws and human trafficking, loosely defined (Cho, Dreher, & Neumayer, 2013; Jakobsson & Kotsadam, 2013). No studies have examined how the simultaneous existence and availability of legal and illegal markets can affect demand for sexual services at the level of individual decision making.…”
mentioning
confidence: 99%
“…This enabled us to consider the treatment of prostitution in France from a new perspective, while exploring at the same time the specificities of Belgian policies, which have so far received little attention in the social sciences. Moreover, comparing two relatively analogous countries neutralized certain differences, while allowing others, more closely linked to our research object, to be analyzed in greater depth (Weitzer 2015). These countries have many sociocultural similarities resulting from their geographical proximity and common use of the French language, while the very general characteristics of the Bsex workers^with whom the third sector organizations in question work are relatively similar.…”
Section: Contextual and Empirical Aspects For A Comparison Between Bementioning
confidence: 99%